Cork-polymer composites: a sustainable solution in injection moulding and additive manufacturing - Silva, Sara Patrícia Magalhães da (2021)
Today, the world that we live in is moving fast towards the Digital, which is causing profound technological mutations. Additive Manufacturing (AM), commonly called “3D printing”, is one of the symbols of these digital and technological effervescence. Initially, AM technologies were only seen as rapid prototyping tools. Nowadays, this stigma has changed and the market began to look at AM technologies as an effective and competitive alternative to the manufacture of products besides the conventional techniques. Cork is the world’s ambassador Portuguese material! A 100% natural material and it presents a unique combination of properties, given its composition and alveolar structure. Low density, hydrophobic character, elasticity and impact resistance are some its properties. This feature makes cork a material high potential in several applications. Wine stoppers is the major application of cork. From this production is generated a large amount of cork residues with different granulometries, where residues with calibres superior than 0.5-1.0 mm are already used in the development of cork-based composites for flooring and insulation applications. The valorisation of these cork residues through the development of new sustainable composite materials was one of the main motivations that triggered the present work. This thesis reports the development of cork-polymer composites (CPC) and cork-based formulations adapted to conventional and AM technologies. It will involve a conventional technology, the injection moulding (IM) technique, and two AM technologies, namely Fused Filament Fabrication (FFF) and 3D Printing (3DP). The preservation of cork alveolar structure after processing by these technologies was always sought. The present thesis is composed by a set of published papers in scientific journals and in conferences. Papers are integrated into two chapters (Chapter II and Chapter III). At the beginning of each chapter, it is presented an introduction to the topic. Chapter II concerns the development of CPC solutions adapted for IM, while Chapter III focus on the development of CPC and cork-based formulations solutions adapted to FFF and 3DP, respectively. Chapter II presents the study of the rheological and the non-isothermal crystallization behaviours of CPC. These studies have shown that the addition of cork did not compromise the flowability of CPC and its processability by IM. In addition, cork powder surface acted as a nucleating agent during non-isothermal crystallization. The presence of a coupling agent based on maleic anhydride (MA) contributed to the development of CPC with enhanced flowability, crystallinity degree and interfacial adhesion between the polymeric matrix and cork particles. A case study related to the effect of the high pressures applied during a standard IM process on the integrity of cork alveoli was performed. The application of low pressures, the removal of holding and back pressures and the use of shut-off nozzles were analysed as an adapted IM solution. Cork alveoli were able to recover from the deformation caused by the IM process, especially when cork granules were near to matrix defects (voids). A promising result which indicates that after an IM process the cork particles can recover its initial shape and size. On the other hand, Chapter III reports (i) the development of a cork-like filament with an incorporation of cork powder equal to 15 % (w/w), which represents 55 % in volume and (ii) the development of cork-based formulations adapted to 3DP. Focusing on the FFF technology, a case study was conducted to evaluate the usefulness and printability of the developed CPC filament. The printed parts exhibited unique characteristics, such as a non-plastic and warm touch, a natural colour and the release of a pleasant odour during the printing process. A case study, based on the 3DP technology, was conducted to evaluate the printability of the developed cork-based formulations. Previously, the applicability of the Washburn Capillary Rise (WCR) method was studied to determine the wettability of cork powders by a commercial binder (≥ 95% (w/w) of water). Cork powders are slightly wetted by the commercial binder (contact angles of () ≈ 86 – 87º). 3DP cork parts with complex geometry were successfully printed. Parts exhibited lightweight and, warmness and softness to the touch. From the available knowledge, it is believed that this was the first time that cork powders were processed by 3DP. In addition, the autoclave technique was also studied and validated as a post-processing phase in the 3DP process. The main conclusions and perspectives of future work are presented in Chapter IV. The present thesis constitutes an original approach for the valorisation of cork powder residues. The combination of a natural and traditional product, such as cork, with high-tech technologies, can lead to the development of cork products never processed before, or to new applications of cork products never thought before.